2009
DOI: 10.1037/a0013829
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of the object recognition deficit associated with perirhinal cortex damage in rats: Effects of varying the lesion extent and the duration of the sample period.

Abstract: The present study examines 2 factors that might moderate the object-recognition deficit seen after perirhinal cortex damage. Object recognition by normal rats was improved by extending (from 4 to 8 min) the sample period during which an object was first explored. Furthermore, there was a significant positive correlation between time spent in close exploration of the sample object and degree of successful novelty discrimination. In contrast, rats with perirhinal cortex lesions failed to benefit from increased c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
108
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(121 citation statements)
references
References 49 publications
11
108
1
1
Order By: Relevance
“…Furthermore the property of one-trial learning makes it suitable for the examination of temporal aspects of memory. Over time, it has become a widely used tool for the assessment of memory functions in combination with pharmacological treatments [6][7][8][9][10] and brain lesions [11][12][13][14]. The ORT is mainly used for rodent experiments, most research is done with rats and mice but the task is also suitable for testing other rodent species [15].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore the property of one-trial learning makes it suitable for the examination of temporal aspects of memory. Over time, it has become a widely used tool for the assessment of memory functions in combination with pharmacological treatments [6][7][8][9][10] and brain lesions [11][12][13][14]. The ORT is mainly used for rodent experiments, most research is done with rats and mice but the task is also suitable for testing other rodent species [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies use flexible sample trial durations, allowing all animals to reach a specific amount of object interaction [12,[30][31][32]. Other experiments have fixed sample trial durations and each individual animal differs in the amount of sample object exposure [1,11,25,33]. Before testing starts, the animals are often familiarized or habituated and protocols differ greatly between laboratories.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the rat, unlike the monkey, structures such as the medial dorsal nucleus receive few, if any, projections from the perirhinal cortex (Groenewegen 1988). If the rat is predominantly reliant on perirhinal familiarity-based processes for standard tests of object recognition, then it is likely that temporal lobe functions are largely sufficient (Mumby and Pinel 1994;Albasser et al 2009Albasser et al , 2010, as the rat perirhinal cortex cannot access the medial diencephalon. Consistent with this interpretation, immediate-early gene imaging studies have found increased c-fos activity for novel visual stimuli in the perirhinal cortex but not in the medial dorsal thalamic nucleus (Zhu et al 1995).…”
Section: Toward a Model Of Diencephalic Contributions To Recognition mentioning
confidence: 99%